Pineal Gland Volume in Major Depressive and Bipolar Disorders - Takahashi, Tsutomu; Sasabayashi, Daiki; Yücel, Murat; Whittle, Sarah; Lorenzetti, Valentina; Walterfang, Mark; Suzuki, Michio; Pantelis, Christos; Malhi, Gin S.; Allen, Nicholas B. (Frontiers in Psychiatry, 2020)
Abnormal melatonin secretion has been demonstrated in patients with affective disorders such as major depressive disorder (MDD) and bipolar disorder (BD). However, magnetic resonance imaging (MRI) studies that previously investigated the volume of the pineal gland, which regulates circadian rhythms by secreting melatonin, in these patients reported inconsistent findings. The present study employed MRI to examine pineal gland volumes and pineal cyst prevalence in 56 MDD patients (29 currently depressed and 27 remitted patients), 26 BD patients, and matched controls (33 for MDD and 24 for BD). Pineal volumes and cyst prevalence in the current MDD, remitted MDD, and BD groups did not significantly differ from those of the healthy controls. However, pineal gland volumes were significantly smaller in the current MDD subgroup of non-melancholic depression than in the melancholic MDD subgroup. Interestingly, pineal volumes correlated negatively with the severity of loss of interest in the current MDD group. Medication and the number of affective episodes were not associated with pineal volumes in the MDD or BD group. While these results do not suggest that pineal volumes reflect abnormal melatonin secretion in affective disorders, they do point to the possibility that pineal abnormalities are associated with clinical subtypes of MDD and its symptomatology.